Table-like magnetocaloric effect and large refrigerant capacity in Nd6Fe13Pd1-xAgx compounds. (March 2021) - Du, Y.S.; Zhang, C.H.; Lu, Y.M.; Li, L.; Li, J.Q.; Ma, L.; Rao, G.H.
Abstract: Table-like magnetocaloric effect is significant for using the Ericsson cycle in the applications of magnetic refrigeration above 20 K. A series of Nd6 Fe13 Pd1- x Ag x ( x = 0.1, 0.2, 0.3, 0.4) compounds were prepared by the arc-melting method, showing a single crystalline phase in the tetragonal Nd6 Fe13 Si-type structure with the space group I 4/ mcm . All of the compounds undergo a first-order magnetic transition from the ferromagnetism to antiferromagnetism with the temperature increases, as well as a metamagnetic transition from antiferromagnetic state to ferromagnetic state induced by an applied field. The table-like magnetocaloric effects with large refrigerant capacities in these compounds have been observed, which is very rare in a single phase. A constant Δ S M in a temperature span of 60 K in the Nd6 Fe13 Pd0.6 Ag0.4 compound can be observed. For a field change of 0–5 T, the peak values of | ΔS M | for the Nd6 Fe13 Pd0.9 Ag0.1, Nd6 Fe13 Pd0.8 Ag0.2, Nd6 Fe13 Pd0.7 Ag0.3 and Nd6 Fe13 Pd0.6 Ag0.4 compounds are estimated to be 4.9 J kg −1 K −1, 4.5 J kg −1 K −1, 3.5 J kg −1 K −1 and 3.4 J kg −1 K −1 with the corresponding refrigerant capacity values of 327 J kg −1, 315 J kg −1, 306 J kg −1 and 289 J kg −1, respectively. The table-like magnetocaloric effect and large working temperature spans make the series of compounds a good candidate for single-phase magnetic refrigeration material at low temperature based on the Ericsson cycle. Highlights: The crystal structure and magnetocaloric effect in the Nd6 Fe13 Pd1- x Ag x compounds have been studied. There are very rich magnetic phase transitions in the Nd6 Fe13 Pd1- x Ag x compounds. A table-like magnetocaloric effect (MCE) with absolute constant Δ S M was obtained.